PENGARUH PERENCANAAN PAJAK, BEBAN PAJAK TANGGUHAN DAN LABA PERLEMBAR SAHAM TERHADAP NILAI PERUSAHAAN - Manihuruk, Fitri Handayani; Irawati, Wiwit (Musytari : Jurnal Manajemen, Akuntansi, dan Ekonomi, 2025)
The government wants maximum tax payments, while companies want to minimize them. Companies carry out tax planning to minimize tax burdens to increase profits by involving deferred tax burdens and earnings per share owned by the company to increase the value of the company. The purpose of this study is to analyze the effect of tax planning, deferred tax burdens and earnings per share on company value. The study uses a quantitative analysis method with secondary data in the form of company financial reports obtained or downloaded from the Indonesia Stock Exchange website. The population used in the study were industrial sector companies listed on the Indonesia Stock Exchange for the 2019-2023 period, and 70 samples were obtained using the Purposive sampling method. In conducting this analysis, the researcher used the help of Eviews software and the results of this study indicate that tax planning has an effect on company value, while deferred tax burdens and earnings per share have no positive and insignificant effect on company value.